Ricosre Model With Question Formulation Technique (QFT): Enhancing Students' Higher Order Thinking Skills (HOTS) and science literacy - Irdalisa Irdalisa; Budhi Akbar; Tuti Marjan Fuadi; Maesaroh Maesaroh; Eka Kartikawati (Postgraduate, University of Mataram, 2024)
The 21st-century learning has undergone a paradigm shift in education from teacher-centered to student-centered. It recently emphasises students' critical and creative thinking abilities, effective communication, innovation, problem-solving, and collaboration. This study examined the Ricosre model's effectiveness with the Question Formulation Technique (QFT) in enhancing students' higher-order thinking skills (HOTS) and science literacy. It involved 296 fifth-grade students from three selected state elementary schools, chosen through cluster random sampling. Each group consisted of 148 students divided into control and experimental groups. Data were collected through multiple-choice and essay instruments and subsequently analysed using multivariate analysis of variance (MANOVA). The research variables were students' higher-order thinking skills (HOTS) and science literacy. The results indicated that the Ricosre model with QFT effectively improves students' higher-order thinking skills (HOTS) and science literacy, as it encouraged active participation during the learning process, trained students to develop questioning skills, find answers, analyse, share ideas, and draw conclusions. Thus, it can foster curiosity and metacognitive abilities among students.